Understanding the psychology of Internet behaviour virtual worlds, real lives - Joinson, Adam N. 1970- (Palgrave Macmillan, 2003)
wide range of topics related to psychology and the Internet, including computer-mediated communication, web browsing and use of the Internet to conduct psychological research